Increasing Importance of Heat Stress for Cattle Farming Under Future Global Climate Scenarios - Vergara-Egert, P; Alaniz-Baeza, A; Carvajal-Leon, M (Elsevier B.V., 2021)
In the last decades, livestock species have been severely affected by heat stress because of increasing temperatures, which has threatened animal welfare and decreased production. Based on thermal comfort indices and ensemble climate projections, we analyzed the current and future global spatiotemporal patterns of the heat exposure of cattle in 10 agroclimatic zones. The results show that ~7% of the global cattle population is currently exposed to dangerous heat conditions. This percentage is projected to increase to ~48% before 2100 under a scenario of growing emissions. Tropical agroclimatic zones are expected to face an early increase in the exposure to intense heat before 2050. Heat exposure was negatively correlated with the socioeconomic variables, showing that poor and livestock-dependent tropical countries are the most affected. Our results demonstrate the near-future consequences of heat stress on livestock, emphasizing the limited time available to implement effective abatement strategies. © 2021